THE EFFECT OF BABY MASSAGE ON BABY GROWTH IN HUTA HOLBUNG VILLAGE, ANGKOLA MUARATAIS DISTRICT, DISTRICT SOUTH TAPANULI - Sinuhaji, Lidya Natalia Br; Purba, Edy Marjuang; Silalahi, Romauli (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2022)
Data from the Central Statistics Agency for North Sumatra Province (2020), the live birth rate is 292,875 babies, seeing the high number of live births in babies it is very important to provide a stimulus during the golden age so that there is no developmental delay. The purpose of this study was to determine the effect of baby massage on infant growth in Huta Holbung Village, Angkola Muaratais District, South Tapanuli Regency. This type of research is Pre Experimental Designs with one group pretest-posttest design. The study was conducted in Huta Holbung Village, carried out from March to June 2021. The population was all infants aged 1-12 months in Huta Holbung Village with a sample of 30 infants, of which 15 were the intervention group and 15 were the control group. Using purposive sampling technique. Data analysis used bivariate analysis with independent statistical test T-test. The average baby weight in the experimental group before the massage was done was 4560 grams and the average after the massage was 5350 grams, which means an increase in body weight of 17.32%, while in the control group the average weight at the beginning of the study was 4556 grams and the average body weight at the end of the study was 5170 grams, which means an increase in body weight of 13.48%. The test results obtained t count 6.221, (p = 0.000), t table 1.753 with a significance of 5%. Because t count is greater than t table (6,221 > 1,753). There is a significant effect of baby massage on the growth of infants aged 0-3 months in Huta Holbung Village, Angkola Muaratis District, South Tapanuli Regency in 2021.